The Impact of The Use of Social Media and Awareness of Religion Due to Influence The Role of The Parents and Teachers in Class Junior High School Student - Muhyani Muhyani (Universitas Sebelas Maret, 2019)
This study is to find purposes: (1) the parents to influence of religious awareness, (2) the effect of parenting on the impact of using social media, (3) the influence of students' perceptions of the role of teachers in schools on religious awareness, (4) the influence of students' perceptions of the role of teachers in schools on the impact of social media users, (5) the influence of religious awareness on the impact of social media users. This research is field research is a social research in education. This research is categorized as survey research (Research Survey) where researchers do not make special treatment to respondents, researchers only distribute questionnaires to respondents. Furthermore, respondents were asked to fill in accordance with what they felt for the statement on the questionnaire. The population in this study were junior high school students in the cities of Depok and Bogor, while the sample in this study were several junior high school students in Depok and Bogor cities consisting of 427 students. Data are analyzed using structural equation models (structural equation models) known as LISREL. The analysis to be carried out in this study is path analysis. The results of this study indicate: (1) parenting directly influences religious awareness, (2) parenting directly influences the impact of social media use, (3) students' perceptions of the role of teachers in schools do not directly influence religious awareness , (4) students' perceptions of the role of teachers in schools directly influence the impact of social media users (5) religious awareness directly influences the impact of social media users.